The hydrogen ambitions of the Gulf States: Achieving economic diversification while maintaining power - Dawud Ansari (Stiftung Wissenschaft und Politik (SWP), 2022)
The countries of the Gulf Cooperation Council (GCC) are mapping out agendas to kickstart a hydrogen economy. Especially Saudi Arabia, Oman, and the United Arab Emirates (UAE) are pursuing ambitious plans to supply Europe and Asia-Pacific with the carbon-friendly fuel. Numerous declarations of intent have been signed, and the first large-scale projects are under way. For the Gulf countries, hydrogen is not only a means of diversification. Since the hydrogen economy blends into the institutional and fiscal framework of the petroleum industry, it is primarily a chance for the GCC economies to maintain current economic and political power structures. While hydrogen from the Gulf is an effective tool for climate change mitigation, Germany and Europe are faced with trade-offs and open questions.
Keywords: 320